Simultaneous Study of Cholesterol and GM1 Ganglioside by Specific Probes: Lipid Distribution during Maturation, Capacitation and the Acrosome Reaction - Boarelli, Paola Vanina (2016)
Lipid distribution has been extensively studied in the plasma membrane of the male gamete due to its relevant role in sperm physiology. However, there are controversial reports about their distribution. Because of different reports about this topic, the aim of this work was define cholesterol and GM1 ganglioside location by simultaneous detection during sperm maturation, capacitation and the acrosome reaction in CF1 mouse sperm. We observed that throughout the epididymis, cholesterol detected by filipin III or complex and GM1 ganglioside by cholera toxin, colocalized in the acrosomal domain of the head and midpiece of the flagellum. During sperm capacitation, a decrease of cholesterol can be observed like diffuse pattern on the whole head, while GM1 ganglioside was restricted to the apical acrosome. Capacitated sperm incubated with acrosome reaction inducers showed a diffuse location on the head with both probes after acrosomal exocytosis. Also, both probes did not show different locations on the flagellum. These findings indicate that cholesterol and GM1 ganglioside have a dynamic behaviour during the life of the sperm, which could indicate that a continuous assembly or disassembly of the lipid raft could be involved in the responsiveness of the sperm to different environments. Thus, during sperm capacitation and acrosome reaction there is a redistribution of the lipids. However, there are not apparent changes during sperm maturation. Cholesterol efflux, a characteristic event of sperm capacitation, could be analyzed through diffuse pattern described by filipin, and GM1 ganglioside patterns observed by the cholera toxin could be interesting when it is needed to evaluate sperm capacitation and the acrosome reaction in fixed sperm